Waiting lists, waiting times and admissions: An empirical analysis at hospital and general practice level - Frank Windmeijer; Hugh Gravell; Pierre Hoonhout (Institute for Fiscal Studies (IFS), 2004)
We report an empirical analysis of the responses of the supply and demand for secondary care to waiting list size and waiting times. Whereas previous empirical analyses have used data aggregated to area level, our analysis is novel in that it focuses on the supply responses of a single hospital and the demand responses of the GP practices it serves, and distinguishes between outpatient visits, inpatient admissions, daycase treatment and emergency admissions. The results are plausible and in line with the theoretical model. For example: the demand from practices for outpatient visits is negatively affected by waiting times and distance to the hospital. Increases in waiting times and waiting lists lead to increases in supply; the supply of elective inpatient admissions is affected negatively by current emergency admissions and positively by lagged waiting list and waiting time. We use the empirical results to investigate the dynamic responses to one off policy measures to reduce waiting times and lists by increasing supply.
Keywords: I11; H42; 330; waiting time; waiting list; hospital admissions; Krankenhaus; Warteschlangentheorie; Großbritannien